VERBS DENOTING AFFECTIVITY PROCESS - Phan Thị Như Gấm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The thesis investigates English and Vietnamese verbs denoting affectivity process in two aspects: semantics and syntax. Some concepts and terms in relation to this linguistic area have been dealt with. Based on the analysis of verbs in terms of functional grammar, affectivity processes have been described and analyzed in the discourse. A contrastive analysis has been carried out so as to explore the similarities and differences of affectivity verbs in the two languages and the frequency of affectivity verbs in English and Vietnamese discourse. Finally, the pedagogical suggestions for teaching and learning verbs denoting affectivity process have been offered in the hope they can benefit the language learning and teaching.